Association Between Low Muscle Mass and Gastric Hyperplastic and Inflammatory Polyps in Chinese Asymptomatic Adult Males - Wang, Na; Chen, Mengjun; Lin, Chunjing; Lin, Weihong (Frontiers in Medicine, 2022)
Background: Gastric polyp is an abnormally proliferative or neoplastic growth of the gastric mucosa, with a degree of tendency to transform into gastric cancer. Lack of physical activity that is significantly related to low muscle mass(LMM) and muscle strength, has been identified to be associated with gastric polyps. In this study, we examine the association of LMM and different histological types of gastric polyps among Chinese asymptomatic adult males. Methods: In all, 1742 male adults undergoing bioelectrical impedance analysis and upper gastrointestinal endoscopies, were included. Univariate and multivariate logistic regression models were used to analyze the effect of LMM on the risk of gastric polyps and different histological types. Results: By univariate and multivariate analyses, LMM(OR:1.691, 95%CI: 1.047-2.729, p=0.032) kept independent effect on risk of gastric polyps. When ratio of appendicular skeletal muscle mass to body mass index(ASM/BMI) was brought into the analyses, it was identified to be negatively correlated with occurrence of gastric polyps(OR: 0.743, 95%CI: 0.566-0.976, p=0.033). For different pathological types, LMM showed different effect on occurrence of gastric polyps. LMM was an independent indicator for hyperplastic and inflammatory polyps(OR: 2.383, 95%CI: 1.291-4.397, p=0.006), rather than fundic gland polyps(OR: 1.013, 95%CI: 0.473-2.173, p=0.973). Conclusion: In generally, LMM was an independent indicator for hyperplastic and inflammatory polyps occurrence in Chinese asymptomatic adult males.